2022
DOI: 10.1111/ajag.13041
|View full text |Cite
|
Sign up to set email alerts
|

Using information and communication technology learnings to alleviate social isolation for older people during periods of mandated isolation: A review

Abstract: Objective To examine the effectiveness of information and communication technologies (ICTs) in reducing social isolation in older people and draw recommendations from previous literature appropriate for informing ICT use in future mandated periods of isolation. Methods A systematically conducted review of key databases to identify studies investigating ICT interventions that targeted social isolation or loneliness among older people. Results Fifteen articles were identified. All articles used ICT as an interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…For example, enhanced levels of gerontological practice, namely “Promoting mental health and psychological well-being”, “Providing evidence-based dementia care”, and “Enabling access to technology”, were positively associated with intentions to work in aged care. Increased uses of technology, such as e-Health, m-Health and social media, have been designed in the development of nursing interventions [ 16 , 17 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, enhanced levels of gerontological practice, namely “Promoting mental health and psychological well-being”, “Providing evidence-based dementia care”, and “Enabling access to technology”, were positively associated with intentions to work in aged care. Increased uses of technology, such as e-Health, m-Health and social media, have been designed in the development of nursing interventions [ 16 , 17 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a small scholarly industry of 'scoping reviews' on care robots for elderly persons, and these reviews invariably identify loneliness as a significant guiding rationale for the development and use of robots for the care of elderly persons (e.g. Agraz et al, 2022;Budak et al, 2021;Hung et al, 2022;Koh et al, 2021;Sather et al, 2021;Todd et al, 2022;Yu et al, 2022). In her biography of loneliness, historian Alberti (2019: vii) notes that we now find ourselves in the midst of a declared loneliness epidemic, necessitating the creation of the Minister of Loneliness in the UK in January 2018: 'Talking about loneliness seems to spread, contagion-like, until it has become part of the social fabric.…”
Section: Imagining Futures Of Carementioning
confidence: 99%
“…On the contrary, Shah et al's systematic review and meta-analysis found no evidence of effectiveness of digital technology interventions on loneliness in older adults ( 44 ). Other reviews expressed caution about mixed evidence of positive effects of technologies on loneliness in older adults ( 45 ) and the need to consider technology as just one intervention that could be beneficial amongst others ( 46 , 47 ). Reviewing the evidence about loneliness and social isolation for older people during the pandemic led Kasar and Karaman to call for greater use of technology, whilst recognising the barriers that some older people face which might be addressed through free communication platforms or simply telephone calls to support them to be socially active ( 48 ).…”
Section: Introductionmentioning
confidence: 99%